PRELIMINARY STUDY ON THE EFFECTS OF 2,4-D HERBICIDE FORMULATIONS ON REEF BUILDING CORALS - A Sabdono; Joetono .; J. Soedarsono; H. Hartiko; W.T. Artama (JOURNAL OF COASTAL DEVELOPMENT, 1998)
The increasing use of herbicides in agriculture sectors have receives great attention with respect to their potential toxic effect on reef-building corals of Indonesia. One chlorinated compound, 2,4-dichloro phenoxy acetat (2,4-D), has widely been used as a herbicide and has become a substantial environment pollutant. Controlled tolerance experiment testing 2,4-D was performed on Porites sp. And Galaxea sp in Marine Station, Teluk Awur, Jepara. The effect 2,4-D on coral mortality and zooxanthellae expulsion were investigated. The result showed that short duration (48 h) laboratory test demonstrated dramatic effect on sloughing and death of coral. The median lethal concentration (LC50-48) was determined to be 23.20 ppm on Porites sp and 10.26 ppm on Galaxea sp. There were no significant differences between Porites sp and Galaxea sp on the toxic response of 2,4-D compounds.